2015
DOI: 10.1021/acs.iecr.5b02500
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Simulation Study of the Solubility, Diffusivity and Permselectivity of Pure and Binary Mixtures of CO2 and CH4 in the Ionic Liquid 1-n-Butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide

Abstract: The knowledge of the mixture solubility and diffusivity of gases in ILs is critical for the design of supported ionic liquid membranes (SILMs). Since mixed gas solubilities and diffusivities in ILs are much more difficult to measure than pure gas properties, pure gas solubility and diffusivity data are typically used along with an ideal solubility/diffusivity assumption to estimate permselectivities. It is not clear, however, if the ideal solubility and diffusivity assumptions are valid. In this work molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 60 publications
3
31
1
Order By: Relevance
“…In current work, the diffusivity of gas penetrants has been determined adopting the means of molecular positioning theory, or more commonly known as the Einstein relationship [18][19][20][21][22][23][24]. In Einstein correlation, he related the self-diffusion coefficient of gas particles i, D i to the mean square displacement (MSD) as a function of observation time, such as that presented in (1), through the assumption of particle random walk [25].…”
Section: Gas Diffusivitymentioning
confidence: 99%
“…In current work, the diffusivity of gas penetrants has been determined adopting the means of molecular positioning theory, or more commonly known as the Einstein relationship [18][19][20][21][22][23][24]. In Einstein correlation, he related the self-diffusion coefficient of gas particles i, D i to the mean square displacement (MSD) as a function of observation time, such as that presented in (1), through the assumption of particle random walk [25].…”
Section: Gas Diffusivitymentioning
confidence: 99%
“…It is worth mentioning that some gases, such as CO 2 , SO 2 and CH 4 , show great solubility in functional ILs. [22][23][24][25][26][27] Their use may be extended to lignocellulose composites. 28,29 These experiments proved that RTILs have effectively promoted the dissolution and catalytic conversion of biomass materials.…”
Section: Introductionmentioning
confidence: 99%
“…7 Numerous research groups have systematically studied the capturing capacity of various ILs for various gases, including CO 2 , CH 4 , H 2 and so on, by both experimental and theoretical approaches. 1,2,[8][9][10][11][12][13][14][15] Ramdin et al experimentally studied the CO 2 solubility and diffusivity in numbers of ILs and proposed that ILs have great solubility capacity to CO 2 . 1 Anthony et al reported that 1-n-butyl-3-methlimidazolium hexauorophosphates have strong dissolving ability for CO 2 .…”
Section: Introductionmentioning
confidence: 99%